Wide distribution of Mediterranean and African spotted fever agents and the first identification of Israeli spotted fever agent in ticks in Uganda - Eneku, Wilfred; Erima, Bernard; Maranda Byaruhanga, Anatoli; Atim, Gladys; Tugume, Titus; Ukuli, Qouilazoni A.; Kibuuka, Hannah; Mworozi, Edison; Christina, Douglas; Jeffrey, W. Koehler; Nora, G. Cleary; Michael, E. von Fricken; et al. (PLOS NEGLECTED TROPICAL DISEASES, 2023)
Rickettsia microorganisms are causative agents of several neglected emerging infectious diseases in humans transmitted by arthropods including ticks. In this study, ticks were collected from four geographical regions of Uganda and pooled in sizes of 1–179 ticks based on location, tick species, life stage, host, and time of collection. Then, they were tested by real-time PCR for Rickettsia species with primers targeting gltA, 17kDa and ompA genes, followed by Sanger sequencing of the 17kDa and ompA genes. Of the 471 tick pools tested, 116 (24.6%) were positive for Rickettsia spp. by the gltA primers. The prevalence of Rickettsia varied by district with Gulu recording the highest (30.1%) followed by Luwero (28.1%) and Kasese had the lowest (14%). Tick pools from livestock (cattle, goats, sheep, and pigs) had the highest positivity rate, 26.9%, followed by vegetation, 23.1%, and pets (dogs and cats), 19.7%. Of 116 gltA-positive tick pools, 86 pools were positive using 17kDa primers of which 48 purified PCR products were successfully sequenced. The predominant Rickettsia spp. identified was R. africae (n = 15) in four tick species, followed by R. conorii (n = 5) in three tick species (Haemaphysalis elliptica, Rhipicephalus appendiculatus, and Rh. decoloratus). Rickettsia conorii subsp. israelensis was detected in one tick pool. These findings indicate that multiple Rickettsia spp. capable of causing human illness are circulating in the four diverse geographical regions of Uganda including new strains previously known to occur in the Mediterranean region. Physicians should be informed about Rickettsia spp. as potential causes of acute febrile illnesses in these regions. Continued and expanded surveillance is essential to further identify and locate potential hotspots with Rickettsia spp. of concern.